CONFIDENCE AND ANXIETY FACING THE COMPETITION OF KYOURUGI TAEKWONDO ATHLETES SALATIGA: A CORRELATION STUDY - Aulya Salsa Happy Wulandari; Emmanuel Satyo Yuwono (Journal of Community Mental Health and Public Policy, 2023)
Background: Anxiety over competition is one of the things that is stressful with mental symptoms associated interpreted as a feeling of anxiety, uneasiness, and worried. Self-confidence is the belief in one's abilities, so one does not feel anxious when carrying out an activity, has a feeling of freedom in doing something one wants, and a sense of responsibility for the decisions and actions taken. Purpose: this study aims to determine whether there is a relationship between self-confidence and competition anxiety among kyourugi taekwondo athletes in Salatiga city. Method: Used was quantitative with a correlation design. A total of 37 kyourugi taekwondo athletes in Koni Salatiga were used as research participants using a saturated sampling techniques. Results: Confidence was measured using the SAS-2 Sport Anxiety Scale (a = 0.901) and competition anxiety was measured using the Self-Confidence Scale (a = 0.907). The results of this study prove that self-confidence and competition anxiety have a negative relationship (r = -0.757 and sig = 0.000). Conclusion: These results mean that the higher the athlete's confidence, the lower the athlete's competition anxiety. Meanwhile, the lower the athlete's self-confidence, the higher the athlete's competition anxiety. Abstrak Latar Belakang: kecemasan menghadapi pertandingan merupakan salah satu hal yang listres dengan gejala mental berkaitan dnegan perasaan yang negatif. Kecemasan menghadapi pertandingan juga dapat diartikan sebagai perasaan gelisah, tidak tenang dan khawatir. Kecemasan mengahdapi pertandingan adalah listres yang dialami oleh seorang atlet yang terjadi ketika meningkatnya emosi negatif pada suatu situasi dalam pertandingan. Kepercayaan diri ialah keyakinan atas kemampuan yang dimiliki, sehingga tidak merasa cemas ketika melakukan suatu kegiatan, memiliki perasaan bebas dalam melakukan sesuatu hal yang diinginkan, dan rasa tanggung jawab atas keputusan dan tindakan yang dilakukan. Tujuan: penelitian ini bertujuan untuk mengetahui adanya hubungan antara kepercayaan diir dan kecemasan menghadapi pertandingan pada atlet kyourugi tekwondo di kota Salatiga. Metode: Metode yang diunakan yaitu kuantitatif dengan design korelasi. Sebanyak 37 atlet kyourugi tekwondo Koni Salatiga dijadikan sebagai partisipan penelitian dengan mengguanakn teknik sampling jenuh. Hasil: kepercayaan diir diukur mengguanakn SAS-2 Sport anxiety Scale (a = 0,901) dan kecemasan bertanding diukur menggunakan Self-Confidence Scale (a = 0,907). Hasil dari penelitian ini membuktikan bahwa kepercayaan diri dan kecemasan bertanding memiliki hubungan negatif (r = -0,757 dan sig = 0,000). Kesimpulan: hasil tersebut memiliki arti bahwa semakin tinggi kepercayaan diri atlet, maka semakin rendah kecemasan bertanding atlet tersebut. Sedangkan, semakin rendah kepercayaan diir atlet. maka semakin tinggi kecemasan bertanding atlet tersebut.